A research proposal on utilization of patient's rights by prisoners at Zomba Central Hospital. - Mshali, Kondwani (Kamuzu University of Health Sciences, 2022)
The purpose of this study is to assess the utilization of patient's rights by prisoners at Zomba Central Hospital. This study will be conducted at the ward for prisoners at the chosen central